049. Recurrence Factors of Early-Stage Colon Cancer Post-Colectomy: A Literature Review - Sultani, Adil; Giamour, Vania Myralda; Mazni, Yarman (JBN (Jurnal Bedah Nasional), 2024)
Background : Colon cancer is more prevalent in men than in women, with an incidence rate of 131/100,000 in men and 10/100,000 in women. The incidence of new cases and mortality has decreased over recent years, except in younger adults (<50 years), which may be associated with increased cancer screening and improved therapeutic modalities. The rise in incidence is linked to obesity, physical inactivity, alcohol consumption, high red meat intake, and smoking. Some data suggest that colon cancer carcinogenesis is related to imbalances in the gut microbiota. The validation of individual risk factors and multivariable predictive models for metastasis, local or distant recurrence, is crucial. This study aims to determine the risk factors for recurrence of early-stage colon cancer post-colectomy. A literature review discussing the factors of colon cancer recurrence. Literature was searched using online databases such as Cochrane, PubMed, EBSCO, and ProQuest. Case: Based on the review of seven studies discussing colon cancer recurrence factors, the statistical results varied, with each article having its own research limitations. Overall, the risk of colon cancer recurrence post-colectomy was present in patients with risk factors discussed in this literature review. Conclusion: Post-colectomy recurrence of colon cancer shows the presence of relapse at the anastomosis site. High-risk patients for early recurrence include those with elevated CA 19-9 levels post-surgery, venous tumor invasion, or advanced N stage. Vitamin D supplementation can be added to standard colorectal cancer treatment. Preoperative CEA levels are an independent prognostic factor for both overall and oncological outcomes.